Do We Need a Specific Guideline for Assessment and Improvement of Acromegaly Patients Adherence? - Kamusheva, Maria; Parvanova, Alexina; Rusenova, Yanitsa; Vandeva, Silvia; Elenkova, Atanaska (Frontiers in Public Health, 2021)
Background: Adherence to therapy is one of the most important elements during the therapeutic process ensuring the predefined therapeutic outcomes. The aim is to analyze the need and importance of treatment adherence guideline for acromegaly patients and the possibilities for its development and implementation in Bulgaria. Methods: A set of methods was applied: (1) a literature review in the electronic database for identification of articles and guidelines related to adherence and acromegaly; (2) analysis of Bulgarian legislative documents; (3) a pilot study for assessment of the level of treatment adherence among hospitalized Bulgarian acromegaly patients in 2018; (4) а plan for development and implementation of specific guideline was created entitled BULMEDACRO - BULgarian guideline for MEdication aDherence assessment and improvement in ACROmegaly. Results: No specific guidelines for evaluation, monitoring, reporting and/or improving adherence in acromegaly patients has been found in the literature. Requirements for regular assessment of the level of adherence, application of appropriate methods for improvement and monitoring are not sufficiently formulated and mandatory. The pilot study confirmed that therapy adherence among Bulgarian patients with acromegaly is relatively high as almost 90% of patients report that they strictly comply with their prescribed treatment regimen. It is necessary, however, a specific guideline focused on the methods for assessment and improvement of adherence, in order to ensure monitoring and follow-up of acromegaly patients. Conclusions: Patients with acromegaly should be the focus of specially designed national programs, initiatives and / or guidelines for regular evaluation and improvement of the adherence level. Despite the difficulties and the lack of an adequate legal basis, successive steps initiated by different stakeholder are needed.